PERAN KEPOLISIAN DALAM PENANGGULANGAN TINDAK PIDANA PEMBEGALAN DI WILAYAH POLRES METRO BEKASI KOTA - Fitri Yani Ulath; Mugiati (Constitutum: Jurnal Ilmiah Hukum, 2024)
Robbery or theft with violence is a criminal act (crime), and robbery has been regulated under Article 365 paragraph (1) of the Indonesian Penal Code (KUHP). Robbery is characterized by the use of violence or threats of violence to seize valuable items from victims, with perpetrators often resorting to injuring or even killing their victims. Factors causing robbery in the jurisdiction of the Metro Bekasi Kota Police include opportunity and intent factors, economic factors, educational factors, and environmental factors. The role of the Police in combating robbery in the jurisdiction of the Metro Bekasi Kota Police includes both preventive and repressive efforts. Preventive efforts by the Metro Bekasi Kota Police in combating robbery include cooperation with the community and the formation of specialized teams. These teams include the Police and Community Partnership Forum (FKPM), Police Partner Communication Center (Senkom Mitra Polri), and Community Awareness Group for Security and Public Order (Pokdar Kamtibmas). Repressive efforts by the Metro Bekasi Kota Police in combating robbery include Precision Patrols conducted during nighttime at specific crime-prone times and the formation of Bhabinkamtibmas teams.